2017
DOI: 10.5740/jaoacint.17-0258
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Assessment of 25-Hydroxyvitamin D Assay Performance: A Vitamin D Standardization Program (VDSP) Interlaboratory Comparison Study

Abstract: The Vitamin D Standardization Program (VDSP) coordinated an interlaboratory study to assess the comparability of measurements of total 25-hydroxyvitamin D [25(OH)D] in human serum, which is the primary marker of vitamin D status. A set of 50 individual donor samples were analyzed by 15 different laboratories representing national nutrition surveys, assay manufacturers, and clinical and/or research laboratories to provide results for total 25(OH)D using both immunoassays (IAs) and LC tandem MS (MS/MS). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…While some studies have published relationships between maternal vitamin D intake and infant atopic outcomes, evaluation of the biomarker of exposure, 25(OH)D, is preferable to an estimate of dietary intake. A further consideration is the considerable variability between different analytical methods used to quantify serum 25(OH)D concentrations . It has been suggested that commercial assays produce more unreliable estimates at the higher and lower ends of the distribution of 25(OH)D concentrations, due to higher limits of detection and cross‐reactivity with downstream metabolites .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have published relationships between maternal vitamin D intake and infant atopic outcomes, evaluation of the biomarker of exposure, 25(OH)D, is preferable to an estimate of dietary intake. A further consideration is the considerable variability between different analytical methods used to quantify serum 25(OH)D concentrations . It has been suggested that commercial assays produce more unreliable estimates at the higher and lower ends of the distribution of 25(OH)D concentrations, due to higher limits of detection and cross‐reactivity with downstream metabolites .…”
Section: Discussionmentioning
confidence: 99%
“…A further consideration is the considerable variability between different analytical methods used to quantify serum 25(OH)D concentrations . It has been suggested that commercial assays produce more unreliable estimates at the higher and lower ends of the distribution of 25(OH)D concentrations, due to higher limits of detection and cross‐reactivity with downstream metabolites . Particular attention should be given to chromatographically resolving minor circulating vitamin D metabolites known to interfere with 25(OH)D assays, especially in paediatric populations .…”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, much progress has been made to reduce bias and enable comparability between laboratories through the Vitamin D standardisation programme (VDSP) [22]. Recently, 15 clinical and research laboratories participated in an inter-laboratory comparison study coordinated by the VDSP; nearly all LC-MS/MS results achieved VDSP criteria (CV ≤ 10% and mean bias ≤ 5% against NIST RMP/Ghent University), whereas only 50% of immunoassays met the criterion for a ≤ 10% CV and only three of eight immunoassays achieved the ≤ 5% bias [23]. It is now widely accepted that a standardised measurement of 25(OH)D is a LC-MS/MS method that is aligned to NIST RMP, with quality assurance certified by DEQAS.…”
Section: Quality Assurance and Standardisation Of 25(oh)d Assaysmentioning
confidence: 99%
“…In 2011, a study was undertaken by the VDSP to determine the baseline of 25OHD assay performance with both immunoassays and LC-MS/MS assays in different laboratory environments (61). The study consisted of each laboratory running 50 patient samples that had 25OHD3, 25OHD2, and 3-epi-25OHD3 concentrations assigned by reference measurement procedures at NIST and at Ghent University on their current 25OHD assay, and the results were compared.…”
Section: Measurement Of 25-hydroxy-vitamin Dmentioning
confidence: 99%
“…They found that 6 out of 8 LC-MS/MS assays passed the VDSCP criteria of ≤10% CV and bias of ≤5%. However, only 4 out of 8 immunoassays passed the ≤10% CV criterion, and only 3 out of 8 passed the ≤5% bias requirement (61). Another VDSCP interlaboratory study is currently underway to see if this performance has improved (62).…”
Section: Measurement Of 25-hydroxy-vitamin Dmentioning
confidence: 99%